The Flipped Ovary Sign in Ovarian Torsion. (1st September 2020) - Sugi, Mark D.; Patel, Anika G.; Yi, Johnny; Patel, Maitray D.
Abstract : The diagnosis of ovarian torsion is challenging and relies mostly on morphologic findings. Occasionally, women or children with acute pelvic pain who have undergone an initial ultrasound (US) evaluation with results interpreted as negative for ovarian torsion will return with recurrent or increasing pain, prompting an US reevaluation. The flipped ovary sign refers to a demonstrable change in the orientation of the ovary on follow‐up US examinations, recognized by changing positions of ovarian landmarks established by follicles, cysts, or masses. This sign is valuable for identifying ovarian torsion in these patients, even in the absence of classic morphologic or Doppler features of ovarian torsion.